2016
DOI: 10.1016/j.jcmgh.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Csf1op/op Mice Lacking Macrophages Are Protected Against the Development of Delayed Gastric Emptying

Abstract: Background & AimsDiabetic gastroparesis is associated with changes in interstitial cells of Cajal (ICC), neurons, and smooth muscle cells in both animal models and humans. Macrophages appear to be critical to the development of cellular damage that leads to delayed gastric emptying (GE), but the mechanisms involved are not well understood. Csf1op/op (Op/Op) mice lack biologically active Csf1 (macrophage colony stimulating factor), resulting in the absence of Csf1-dependent tissue macrophages. We used Csf1op/op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 22 publications
5
59
1
Order By: Relevance
“…16, 18 Furthermore, we recently reported that diabetic CSF1 op/op mice, which lack macrophages, never develop delayed gastric emptying and have normal ICC networks. 17 Based on these previous observations, we hypothesized that activated M1 macrophages secrete injurious pro-inflammatory mediators that can damage ICC. In this study, we provided evidence supporting the hypothesis that activated M1 macrophages can directly alter ICC survival and contribute to the pathophysiology of motility disorders such as diabetic gastroparesis where damage to ICC networks is observed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…16, 18 Furthermore, we recently reported that diabetic CSF1 op/op mice, which lack macrophages, never develop delayed gastric emptying and have normal ICC networks. 17 Based on these previous observations, we hypothesized that activated M1 macrophages secrete injurious pro-inflammatory mediators that can damage ICC. In this study, we provided evidence supporting the hypothesis that activated M1 macrophages can directly alter ICC survival and contribute to the pathophysiology of motility disorders such as diabetic gastroparesis where damage to ICC networks is observed.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that CD206-negative macrophages are required for development of delayed gastric emptying in diabetic mice, as diabetic osteopetrotric (CSF1 op/op ) mice, which lack gastric macrophages due to a mutation in the macrophage colony stimulating factor (CSF1), never develop delayed gastric emptying and have normal ICC networks. 17 These data suggest that macrophages are needed to induce damage to ICC networks, resulting in delayed gastric emptying.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, gastric emptying delay was evident only after M2 macrophages phenotypically switched to pro‐inflammatory (M1 or classically activated) macrophages and ICC were lost. In another study using diabetic, macrophage‐deficient CSF1 op/op mice, absence of muscle layer macrophages was protective against the development of delayed gastric emptying . These data suggest that interactions between the innate immune system, specifically macrophages, and ICC and the neuromuscular apparatus may be central in the pathophysiology of human gastroparesis …”
Section: Introductionmentioning
confidence: 87%
“…Targeting macrophages may be an effective therapeutic option to prevent cellular damage and development of delayed gastric emptying in diabetes [2].…”
Section: Journal Of Gastrointestinal and Digestive Systemmentioning
confidence: 99%